The Application of Deep Brain Stimulation for Progressive Supranuclear Palsy: A Systematic Review - Wen, Yafei; Jiao, Bin; Zhou, Yafang (Frontiers in Neurology, 2022)
Progressive supranuclear palsy (PSP) is a rare neurodegenerative disease and currently no effective symptomatic or neuroprotective treatment is available for PSP. Deep brain stimulation (DBS), as a neurosurgical procedure, plays a role in a range of neurological and psychiatric disorders, and a series of case reports have applied DBS in PSP patients. However, there are no systematic investigations about the application of DBS in PSP patients, we therefore performed a systematic review to evaluate the efficacy of DBS for PSP. PubMed, EMBASE and Cochrane library were systematically searched from database inception to July 31, 2021. Additional, reference lists of included studies were hand-searched. Of 155 identified studies, 14 were eligible and were included in our analysis (N = 39 participants). We assessed the data between DBS-OFF and DBS-ON conditions, as measured by the Unifed Parkinson Disease Rating Scale (UPDRS) and other clinical rating scales. A reduction of UPDRS Ⅲ scores under DBS-ON conditions in most PSP cases was observed, but the differences yielded no statistical significance. There wasn’t sufficient evidence proving DBS was effective for PSP patients though part of PSP cases could benefit from DBS, and our findings could give up-to-date information about the possible role of DBS in PSP which would provide design strategies for following clinical trials and might ultimately help to promote the clinical application of DBS in PSP patients.